Media consumption and mental health during COVID-19 lockdown: a UK cross-sectional study across England, Wales, Scotland and Northern Ireland - Neill, Ruth D (Z Gesundh Wiss, 2021)
AIM: As individuals adjust to new ‘norms’ and ways of living during the COVID-19 lockdown, there is a continuing need for up-to-date information and guidance. Evidence suggests that frequent media exposure is related to a higher prevalence of mental health problems, especially anxiety and depression. The aim of this study was to determine whether COVID-19 related media consumption is associated with changes in mental health outcomes. METHODS: This paper presents baseline data from the COVID-19 Psychological Wellbeing Study. The cross-sectional study data was collected using an online survey following the Generalised Anxiety Disorder scale (GAD-7) and the Patient Health Questionnaire (PHQ-9), with some other basic information collected. Logistic regression analysis was used to examine the influence of socio-demographic and media specific factors on anxiety and depression. RESULTS: The study suggested that media usage is statistically significantly associated with anxiety and depression on the GAD-7 and PHQ-9 scales with excessive media exposure related to higher anxiety and depression scores. CONCLUSION: This study indicated that higher media consumption was associated with higher levels of anxiety and depression. Worldwide it should be acknowledged that excessive media consumption, particularly social media relating to COVID-19, can have an effect on mental health. However, as this was a cross-sectional study we cannot infer any directionality as we cannot infer cause and effect; therefore, future research involving longitudinal data collection and analyses of variables over time is warranted.